Demographic Drivers of Environmental Pollution Perception in Nigeria: A Quantitative Analysis - Lawal, Moshood Babatunde; Alausa, Jamiu Abiodun; Nuhu, Zaliha A. (NIU Journal of Social Sciences; Vol 11 No 4 (2025): NIU Journal of Social Sciences, Vol. 11 No. 4, December 2025, 2025)
This study investigates the relationship between demographic factors such as age, education level, gender and geographical factors-location in terms of rural and urban, and people's perceptions of pollution in Nigeria, using data from Afro barometer Round 9. Employing descriptive and inferential statistical analyses (independent t-test, analysis of variance, and the Pearson product-moment correlation coefficient), the study reveals significant regional disparities in pollution perception (F (5,1599) = 26.676; p <.01) with no notable age-based differences. Key findings include positive correlations between pollution concern and male gender (r = .058, p < .001), higher education levels (r = .051, p < .001), urban residence, and regions such as the Northeast and Southeast. Sanitation (26.1% and plastic waste (26.6%) emerged as the most pressing environmental issues. The study underscores the need for tailored policies and community-specific awareness campaigns to address pollution effectively in the country. The implications of the findings for better pollution management were highlighted, and necessary recommendations were made based on these findings Keywords : Environmental Pollution, Demographic Factors, Public Perception, Regional Disparities and Nigeria